2022
DOI: 10.3390/designs6020033
|View full text |Cite
|
Sign up to set email alerts
|

Product Tests in Virtual Reality: Lessons Learned during Collision Avoidance Development for Drones

Abstract: Virtual reality (VR) and real-world simulations have become an important tool for product development, product design, and product tests. Product tests in VR have many advantages, such as reproducibility and shortened development time. In this paper, we investigate the virtual testing of a collision avoidance system for drones in terms of economic benefits. Our results show that virtual tests had both positive and negative effects on the development, with the positive aspects clearly predominating. In summary,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The developed physical model assumed that the system dynamics are impacted by mechanical actions (values and moments of gravitational, propulsion and reactive forces resulting from the aircraft's contact with the cart's surface, as well as aerodynamic force values and moments acting upon the aircraft), and take-off cart magnetic levitation forces associated with the Meissner effect. As demonstrated in [23,26], levitation force values and moments depend on the strength and orientation of the magnetic field generated by launcher tracks, as well as the position and orientation of levitating superconductors. The levitation force resultant acting upon the take-off cart has been modeled as the total value and moment of forces acting upon four boxes of the take-off cart [24].…”
Section: System Dynamics Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…The developed physical model assumed that the system dynamics are impacted by mechanical actions (values and moments of gravitational, propulsion and reactive forces resulting from the aircraft's contact with the cart's surface, as well as aerodynamic force values and moments acting upon the aircraft), and take-off cart magnetic levitation forces associated with the Meissner effect. As demonstrated in [23,26], levitation force values and moments depend on the strength and orientation of the magnetic field generated by launcher tracks, as well as the position and orientation of levitating superconductors. The levitation force resultant acting upon the take-off cart has been modeled as the total value and moment of forces acting upon four boxes of the take-off cart [24].…”
Section: System Dynamics Modelmentioning
confidence: 98%
“…On the other hand, VR technology is increasingly being used to create 3D models and visualizations for virtual prototyping. For example, article [22] addressed the issue of remote and immersive control of UAVs based on VR, while [23] undertook the development of bionic sensor systems for visual detection of UAV collisions. This article presents a new way of presenting engineering simulation results using a VR environment.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue on the "Unmanned Aerial System (UAS) Modeling, Simulation and Control-Part I" focuses on publishing original manuscripts and literature review papers in the areas of UAS modeling, simulation, robust control, artificial intelligent control, design, aerodynamics, aeroelasticity, morphing systems, trajectory optimization, flight tests, wind tunnel tests and other areas closely related to UAS technology improvement. This Special Issue presents research on various UASs and other systems, including the UAS-S45 from the Mexican company Hydra Technologies [1], quadrotors [2,3], drone collision avoidance systems [4], Remotely Piloted Aircraft Systems (RPASs) in [5] and satellite trajectories tracking by radar [6].…”
mentioning
confidence: 99%
“…In ''Product Tests in Virtual Reality: Lessons Learned during Collision Avoidance Development for Drones" [4], the Virtual Reality (VR) testing of a collision avoidance system for drones was investigated and further analyzed in terms of economic benefits. The obtained results have shown that VR tests had benefits expressed in terms of the reduction in the development time, risks and, therefore, costs of the drone collision-avoidance system.…”
mentioning
confidence: 99%